Outcomes and the Role of Primary Histology Following LINAC-based Stereotactic Radiation for Sarcoma Brain Metastases. (May 2020) - Sim, Austin J.; Ahmed, Kamran A.; Keller, Andrew; Figura, Nicholas B.; Oliver, Daniel E.; Sarangkasiri, Siriporn; Robinson, Timothy J.; Johnstone, Peter A.S.; Yu, Hsiang-Hsuan Michael; Naghavi, Arash O.
Abstract : Objectives: The brain is a rare site for sarcoma metastases. Sarcoma's radioresistance also makes standard whole-brain radiotherapy less appealing. We hypothesize that stereotactic radiation techniques (stereotactic radiosurgery [SRS]/stereotactic fractionated radiotherapy [FSRT]) may provide effective local control. Materials and Methods: This single-institution retrospective analysis evaluated our experience with linear acceleator-based SRS/FSRT for sarcoma brain metastases. Time to event analysis was estimated via Kaplan-Meier. Univariable/multivariable Cox regression analyses followed to assess the impact of patient and disease characteristics on outcomes. Results: Between 2003 and 2018, 24 patients were treated with 34 courses of SRS/FSRT to 58 discrete lesions. The median age at first treatment was 57 years (range: 25 to 87 y). Majority of patients had concurrent lung metastases (n=21; 88%), diagnosed spindle cell sarcoma (n=15; 25%) or leiomyosarcoma (n=12; 21%) histology, and were treated with either SRS (n=43; median dose=19 Gy, range: 15 to 24 Gy) or FSRT (n=17; 3/5 fractions, median dose=25 Gy, range: 25 to 35 Gy). With a median follow-up after brain metastasis of 7.3 months, the 6 month/12 month local control, distant brain control, and overall survival of 89%/89%, 59%/34%, and 50%/38%, respectively. All local failures were of primary spindle cell histology ( P <0.001), which was associated with poorer distant control (hazard ratio=25.8, 95% confidence interval: 3.1-536.4; P =0.003) on univariable analysis, and OS (hazard ratio=7.1, 95% confidence interval: 2.0-26.1; P =0.003) on multivariable analysis. Conclusions: This is the largest patient cohort with sarcoma brain metastases treated with SRS/FSRT, it provides durable local control, despite a reputation for radioresistance. Further prospective evidence is required to determine the impact of primary histology on control and survival following brain metastasis diagnosis.